Modified asphalt mortar for road repair and preparation method thereof
By mixing asphalt with modified epoxy polymer, modified quartz sand and modified cage polysilsesquioxane, introducing furan and maleimide groups to achieve self-healing effect, and improving waterproofing ability through fluorination treatment, the problem of the lack of self-healing ability of existing asphalt pavement repair materials is solved, and efficient self-healing and durability of modified asphalt mortar is achieved.
Patent Information
- Application Number
- CN202510329121.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The existing asphalt pavement repair materials lack self-repairing capabilities, resulting in cracks and pits that are prone to reappearance after repair, affecting the durability of the road surface and driving safety.
Modified asphalt mortar is made by mixing asphalt with modified epoxy polymer, modified quartz sand and modified cage polysilsesquioxane, and furyl groups and maleimide groups are introduced to generate reversible bonds, achieving self-healing effects, and improving waterproofing ability through fluorination treatment.
Modified asphalt mortar has good self-repair ability, can resist deformation and damage at high temperatures, improve the heat resistance and aging resistance of the road surface, and at the same time enhance waterproof performance, extend the service life of the road surface and improve driving safety.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of asphalt mortar, in particular to a modified asphalt mortar for road repair and a preparation method thereof. Background Art
[0002] Asphalt pavement is the main form of paving on my country's roads. Compared with cement concrete pavement, asphalt pavement has the advantages of high flatness, no joints, low noise, low dust generation, short construction period, and easy maintenance, and is widely used.
[0003] With the increase of traffic volume and service time, asphalt pavement is prone to looseness, cracks, subsidence, potholes and other defects. If not repaired in time, cars will easily be bumpy when passing by. Under the action of rain and vehicle load, the damage will further expand and even penetrate into the base layer, affecting the durability and service life of the asphalt pavement and threatening driving safety. Therefore, this application introduces a modified asphalt mortar with self-repairing ability. Summary of the invention
[0004] The purpose of the present invention is to provide a modified asphalt mortar for road repair and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] A modified asphalt mortar for road repair, wherein the modified asphalt mortar for road repair is prepared by heating asphalt and mixing it with a modified epoxy polymer, modified quartz sand and modified cage-like polysilsesquioxane; The modified epoxy polymer is prepared by polymerizing glycidyl methacrylate, N,N-dimethylpropyleneamine, and 2-allylfuran and then reacting with N-(trifluoromethylthio)phthalimide; The modified quartz sand is prepared by reacting quartz sand with 3-aminopropyltrimethoxysilane and maleic anhydride in sequence; The modified caged polysilsesquioxane is prepared by reacting 4-propyleneoxy-2-hydroxybenzophenone with octaaminopropyl caged polysilsesquioxane.
[0006] A method for preparing modified asphalt mortar for road repair, the method for preparing modified asphalt mortar for road repair mainly comprises the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:20-22, stirred at 200-300 r / min and room temperature for 5-7 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 45-55°C, and stirring was continued for 3.5-4.5 h under argon protection, filtered, washed with ethanol 3-5 times, and dried to obtain a modified caged polysilsesquioxane; (2) Pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 3-5:1:16-18, stirred for 25-35 min at 85-95 °C, 200-300 r / min, and nitrogen protection, and a mixed solution of 1.8-2.2 times the mass of maleic anhydride was added, and the mixture was stirred for 35-45 min. The mixture was cooled to room temperature, poured into deionized water at 0-4 °C, and stirred for 11-13 h. The mixture was filtered and dried at 75-85 °C for 9-11 h to obtain modified quartz sand. (3) immersing the pre-modified epoxy polymer in a mixed solution of N-(trifluoromethylthio)phthalimide, irradiating with ultraviolet light for reaction, taking out, immersing in deionized water, ultrasonicating for 10 to 20 minutes, and drying at -10 to 0°C under vacuum conditions for 22 to 24 hours to obtain a modified epoxy polymer; (4) Allow the asphalt to stand at 130-140°C for 10-20 min, then add modified quartz sand, modified epoxy polymer and modified cage polysilsesquioxane in sequence, stir at 700-900 r / min for 35-45 min, cool to 85-95°C, and allow to stand for 35-45 min to obtain asphalt mortar.
[0007] As an optimization, the specific operation of the drying in step (1) is vacuum drying at -10~0°C for 22~26h.
[0008] As an optimization, the pre-modified quartz sand in step (2) is prepared by mixing quartz sand, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 3-5:1-2:30-50, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging, taking the solid, washing it with deionized water for 3-5 times, and drying it at 90-100°C for 2-4 hours.
[0009] As an optimization, the quartz sand is 20 mesh quartz sand.
[0010] As an optimization, the mixed solution in step (2) is prepared by uniformly mixing nickel acetate tetrahydrate, triethylamine and acetic anhydride in a mass ratio of 0.001:0.3~0.4:40~45.
[0011] As an optimization, the pre-modified epoxy polymer in step (3) is prepared by mixing glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran in a mass ratio of 7-8:1:1-2:0.03-0.05:30-40, stirring at 200-300 r / min, 60-70°C, under nitrogen protection for 10-12 h, cooling to room temperature, pouring into methanol, standing for 3-5 h, filtering, and vacuum drying at 55-65°C for 22-26 h.
[0012] As an optimization, the N-(trifluoromethylthio)phthalimide mixed solution in step (3) is prepared by uniformly mixing N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone in a mass ratio of 7-8:49-53:0.5-1.
[0013] As an optimization, the specific operation of the ultraviolet light irradiation reaction in step (3) is to place the reaction mixture in a closed photoreactor under nitrogen protection and irradiate it with a 40W purple LED lamp with a wavelength of 370nm for 48 to 50 hours.
[0014] As an optimization, the raw material composition ratio of the asphalt mortar prepared in step (4) is specifically asphalt: modified epoxy polymer: modified quartz sand: modified cage-like polysilsesquioxane in a mass ratio of 8~10: 1.8~2.2: 2.6~3: 0.6~0.8.
[0015] The asphalt is No. 70 Grade A road asphalt, and the purchaser is Xingtai Jiheng Technology Co., Ltd.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the modified asphalt mortar for road repair, the present invention comprises the following steps: reacting 4-propyleneoxy-2-hydroxybenzophenone with octaaminopropyl caged polysilsesquioxane to obtain the modified caged polysilsesquioxane; reacting quartz sand with 3-aminopropyltrimethoxysilane and maleic anhydride in sequence to obtain the modified quartz sand; polymerizing glycidyl methacrylate, N,N-dimethylpropyleneamine and 2-allylfuran and then reacting with N-(trifluoromethylthio)phthalimide to obtain the modified epoxy polymer; and heating asphalt and mixing it with the modified epoxy polymer, the modified quartz sand and the modified caged polysilsesquioxane to obtain the modified asphalt mortar for road repair.
[0017] First, 4-propyleneoxy-2-hydroxybenzophenone is reacted with octaaminopropyl caged polysilsesquioxane to obtain a modified caged polysilsesquioxane; the octaaminopropyl caged polysilsesquioxane can form a tight, high-density hard coating to prevent liquid from penetrating into the interior of the material and enhance the waterproof ability of the material; and the surface of the octaaminopropyl caged polysilsesquioxane is rich in aminopropyl groups, which reacts with epoxy groups to play a curing agent effect. The introduction of the octaaminopropyl caged polysilsesquioxane increases the cross-linking point density of the material, so that the material can better resist deformation and damage at high temperatures, thereby improving its heat resistance, and the octaaminopropyl caged polysilsesquioxane itself has high heat resistance, and its initial thermal decomposition temperature can reach more than 350°C, which can effectively improve the heat resistance of the material; and the introduction of 4-propyleneoxy-2-hydroxybenzophenone through the reaction of amino groups and alkenes can absorb ultraviolet rays, and by absorbing ultraviolet light and converting it into heat energy, the effect of protecting the material from damage by ultraviolet rays is achieved, thereby improving the aging resistance of the material.
[0018] Secondly, quartz sand is reacted with 3-aminopropyltrimethoxysilane and maleic anhydride in sequence to obtain modified quartz sand; glycidyl methacrylate, N,N-dimethylpropyleneamine, and 2-allylfuran are polymerized and then reacted with N-(trifluoromethylthio)phthalimide to obtain a modified epoxy polymer; the asphalt is heated and mixed with the modified epoxy polymer, modified quartz sand, and modified caged polysilsesquioxane to obtain modified asphalt mortar for road repair; furan groups and maleimide groups are introduced into the asphalt mortar, and reversible bonds are generated through the DA reaction between the two to achieve a self-healing effect; fluorine is added to the asphalt surface through the reaction with N-(trifluoromethylthio)phthalimide. The electronegativity of the fluorine atom is very large, so that the electron cloud in the carbon-fluorine bond is biased towards the fluorine atom, resulting in the carbon-fluorine bond having a very high bond energy, which is very stable and not easily destroyed by water or other chemicals, thereby enhancing the material's waterproof ability. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: A method for preparing modified asphalt mortar for road repair, mainly comprising the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:20, stirred at 200 r / min and room temperature for 5 min, an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 45°C, and stirring was continued for 3.5 h under argon protection, filtered, washed with ethanol 3 times, and vacuum dried at -10°C for 22 h to obtain a modified caged polysilsesquioxane; (2) Nickel acetate tetrahydrate, triethylamine and acetic anhydride were mixed in a mass ratio of 0.001:0.3:40 to obtain a mixed solution; quartz sand, 3-aminopropyltrimethoxysilane and isopropanol were mixed in a mass ratio of 3:1:30, stirred at 85°C and 200 r / min for 5 h, centrifuged, the solid was taken, washed with deionized water 3 times, and dried at 90°C for 2 h to obtain pre-modified quartz sand; pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 3:1:16, stirred at 85°C and 200 r / min under nitrogen protection for 25 min, 1.8 times the mass of maleic anhydride was added to the mixed solution, stirring was continued for 35 min, cooled to room temperature, poured into deionized water at 0°C, stirring was continued for 11 h, filtered, and dried at 75°C for 9 h to obtain modified quartz sand; (3) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 7:1:1:0.03:30, stirred at 200 r / min, 60°C, and nitrogen protection for 10 h, cooled to room temperature, poured into methanol, allowed to stand for 3 h, filtered, and vacuum dried at 55°C for 22 h to obtain a pre-modified epoxy polymer; N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone were mixed in a mass ratio of 7:1:1:0.03:30, stirred at 200 r / min, 60°C, and nitrogen protection for 10 h, cooled to room temperature, poured into methanol, allowed to stand for 3 h, filtered, and vacuum dried at 55°C for 22 h to obtain a pre-modified epoxy polymer; 7:49:0.5, mixed evenly to obtain a N-(trifluoromethylthio)phthalimide mixed solution; immersing the pre-modified epoxy polymer in the N-(trifluoromethylthio)phthalimide mixed solution, placing it in a closed photoreactor under nitrogen protection, irradiating it with a 40W purple LED lamp with a wavelength of 370nm for 48 hours, taking it out, immersing it in deionized water, ultrasonicating it for 10 minutes, and drying it at -10°C under vacuum conditions for 22 hours to obtain a modified epoxy polymer; (4) Take 8 parts of No. 70 Grade A road asphalt, 1.8 parts of modified epoxy polymer, 2.6 parts of modified quartz sand, and 0.6 parts of modified caged polysilsesquioxane by mass, let the No. 70 Grade A road asphalt stand at 130°C for 10 min, add modified quartz sand, modified epoxy polymer and modified caged polysilsesquioxane in sequence, stir at 700 r / min for 35 min, cool to 85°C, and let stand for 35 min to obtain asphalt mortar.
[0021] Embodiment 2: A method for preparing modified asphalt mortar for road repair, mainly comprising the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:21, stirred at 250 r / min and room temperature for 6 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 50°C, and stirring was continued for 4 h under argon protection, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 24 h to obtain a modified caged polysilsesquioxane; (2) Nickel acetate tetrahydrate, triethylamine and acetic anhydride were mixed in a mass ratio of 0.001:0.35:42.5 to obtain a mixed solution; quartz sand, 3-aminopropyltrimethoxysilane and isopropanol were mixed in a mass ratio of 4:1.5:40, stirred at 90°C and 250 r / min for 6 hours, centrifuged, the solid was taken, washed with deionized water 4 times, and dried at 95°C for 3 hours to obtain pre-modified quartz sand; pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 4:1:17, stirred at 90°C and 250 r / min under nitrogen protection for 30 minutes, and a mixed solution twice the mass of maleic anhydride was added, and stirring was continued for 40 minutes. The mixture was cooled to room temperature, poured into deionized water at 2°C, and stirring was continued for 12 hours. The mixture was filtered and dried at 80°C for 10 hours to obtain modified quartz sand; (3) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; The pre-modified epoxy polymer was immersed in the N-(trifluoromethylthio)phthalimide mixed solution, and placed in a closed photoreactor under nitrogen protection, and illuminated with a 40W purple LED lamp with a wavelength of 370nm for 49 hours, and then taken out and immersed in deionized water, and ultrasonicated for 15 minutes, and dried at -5°C under vacuum for 23 hours to obtain a modified epoxy polymer. (4) Take 9 parts of No. 70 Grade A road asphalt, 2 parts of modified epoxy polymer, 2.8 parts of modified quartz sand and 0.7 parts of modified caged polysilsesquioxane by mass, let the No. 70 Grade A road asphalt stand at 135°C for 15 min, add modified quartz sand, modified epoxy polymer and modified caged polysilsesquioxane in sequence, stir at 800 r / min for 40 min, cool to 90°C and let stand for 40 min to obtain asphalt mortar.
[0022] Embodiment 3: A method for preparing modified asphalt mortar for road repair, mainly comprising the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:22, stirred at 300 r / min and room temperature for 7 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 55°C, and stirring was continued for 4.5 h under argon protection, filtered, washed with ethanol 5 times, and vacuum dried at 0°C for 26 h to obtain modified caged polysilsesquioxane; (2) Nickel acetate tetrahydrate, triethylamine and acetic anhydride were mixed in a mass ratio of 0.001:0.4:45 to obtain a mixed solution; quartz sand, 3-aminopropyltrimethoxysilane and isopropanol were mixed in a mass ratio of 5:2:50, stirred at 95°C, 300 r / min for 7 hours, centrifuged, the solid was taken, washed with deionized water 5 times, and dried at 100°C for 4 hours to obtain pre-modified quartz sand; pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 5:1:18, stirred at 95°C, 300 r / min, and nitrogen protection for 35 minutes, and a mixed solution of 2.2 times the mass of maleic anhydride was added, and stirring was continued for 45 minutes. The mixture was cooled to room temperature, poured into deionized water at 4°C, and stirred for 13 hours. The mixture was filtered and dried at 85°C for 11 hours to obtain modified quartz sand; (3) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 8:1:2:0.05:40, stirred at 300 r / min, 70°C, and nitrogen protection for 12 h, cooled to room temperature, poured into methanol, allowed to stand for 5 h, filtered, and vacuum dried at 65°C for 26 h to obtain a pre-modified epoxy polymer; N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone were mixed in a mass ratio of 8:1:2:0.05:40, stirred at 300 r / min, 70°C, and nitrogen protection for 12 h, cooled to room temperature, poured into methanol, allowed to stand for 5 h, filtered, and vacuum dried at 65°C for 26 h to obtain a pre-modified epoxy polymer; The pre-modified epoxy polymer was immersed in the N-(trifluoromethylthio)phthalimide mixed solution, placed in a closed photoreactor under nitrogen protection, illuminated with a 40W purple LED lamp with a wavelength of 370nm for 50 hours, taken out, immersed in deionized water, ultrasonicated for 20 minutes, and dried at 0°C under vacuum for 24 hours to obtain a modified epoxy polymer; (4) Take 10 parts of No. 70 Grade A road asphalt, 2.2 parts of modified epoxy polymer, 3 parts of modified quartz sand and 0.8 parts of modified caged polysilsesquioxane by mass, let the No. 70 Grade A road asphalt stand at 140°C for 20 min, add modified quartz sand, modified epoxy polymer and modified caged polysilsesquioxane in sequence, stir at 900 r / min for 45 min, cool to 95°C and let stand for 45 min to obtain asphalt mortar.
[0023] Comparative Example 1: A method for preparing modified asphalt mortar for road repair mainly comprises the following preparation steps: (1) Nickel acetate tetrahydrate, triethylamine and acetic anhydride were mixed uniformly in a mass ratio of 0.001:0.35:42.5 to obtain a mixed solution; quartz sand, 3-aminopropyltrimethoxysilane and isopropanol were mixed in a mass ratio of 4:1.5:40, stirred at 90°C and 250 r / min for 6 hours, centrifuged, the solid was taken, washed with deionized water 4 times, and dried at 95°C for 3 hours to obtain pre-modified quartz sand; pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 4:1:17, stirred at 90°C and 250 r / min under nitrogen protection for 30 minutes, and a mixed solution twice the mass of maleic anhydride was added, and stirring was continued for 40 minutes. The mixture was cooled to room temperature, poured into deionized water at 2°C, and stirring was continued for 12 hours. The mixture was filtered and dried at 80°C for 10 hours to obtain modified quartz sand; (2) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; The pre-modified epoxy polymer was immersed in the N-(trifluoromethylthio)phthalimide mixed solution, and placed in a closed photoreactor under nitrogen protection, and illuminated with a 40W purple LED lamp with a wavelength of 370nm for 49 hours, and then taken out and immersed in deionized water, and ultrasonicated for 15 minutes, and dried at -5°C under vacuum for 23 hours to obtain a modified epoxy polymer. (3) Take 9 parts of No. 70 Grade A road asphalt, 2 parts of modified epoxy polymer, 2.8 parts of modified quartz sand and 0.7 parts of 1,4-butanediamine by mass, let the No. 70 Grade A road asphalt stand at 135°C for 15 min, add modified quartz sand, modified epoxy polymer and 1,4-butanediamine in sequence, stir at 800 r / min for 40 min, cool to 90°C, and let stand for 40 min to obtain asphalt mortar.
[0024] Comparative Example 2: A method for preparing modified asphalt mortar for road repair mainly comprises the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:21, stirred at 250 r / min and room temperature for 6 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 50°C, and stirring was continued for 4 h under argon protection, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 24 h to obtain a modified caged polysilsesquioxane; (2) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; The pre-modified epoxy polymer was immersed in the N-(trifluoromethylthio)phthalimide mixed solution, and placed in a closed photoreactor under nitrogen protection, and illuminated with a 40W purple LED lamp with a wavelength of 370nm for 49 hours, and then taken out and immersed in deionized water, and ultrasonicated for 15 minutes, and dried at -5°C under vacuum for 23 hours to obtain a modified epoxy polymer. (3) Take 9 parts of No. 70 Grade A road asphalt, 2 parts of modified epoxy polymer, 2.8 parts of quartz sand and 0.7 parts of modified caged polysilsesquioxane by mass, let the No. 70 Grade A road asphalt stand at 135°C for 15 min, add quartz sand, modified epoxy polymer and modified caged polysilsesquioxane in sequence, stir at 800 r / min for 40 min, cool to 90°C and let stand for 40 min to obtain asphalt mortar.
[0025] Comparative Example 3: A method for preparing modified asphalt mortar for road repair mainly comprises the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:21, stirred at 250 r / min and room temperature for 6 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 50°C, and stirring was continued for 4 h under argon protection, filtered, washed with ethanol 4 times, and vacuum dried at -5°C for 24 h to obtain a modified caged polysilsesquioxane; (2) Nickel acetate tetrahydrate, triethylamine and acetic anhydride were mixed in a mass ratio of 0.001:0.35:42.5 to obtain a mixed solution; quartz sand, 3-aminopropyltrimethoxysilane and isopropanol were mixed in a mass ratio of 4:1.5:40, stirred at 90°C and 250 r / min for 6 hours, centrifuged, the solid was taken, washed with deionized water 4 times, and dried at 95°C for 3 hours to obtain pre-modified quartz sand; pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 4:1:17, stirred at 90°C and 250 r / min under nitrogen protection for 30 minutes, and a mixed solution twice the mass of maleic anhydride was added, and stirring was continued for 40 minutes. The mixture was cooled to room temperature, poured into deionized water at 2°C, and stirring was continued for 12 hours. The mixture was filtered and dried at 80°C for 10 hours to obtain modified quartz sand; (3) Glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran were mixed in a mass ratio of 7.5:1:1.5:0.04:35, stirred at 250 r / min, 65°C, and nitrogen protection for 11 h, cooled to room temperature, poured into methanol, allowed to stand for 4 h, filtered, and vacuum dried at 60°C for 24 h to obtain a pre-modified epoxy polymer; (4) Take 9 parts of No. 70 Grade A road asphalt, 2 parts of pre-modified epoxy polymer, 2.8 parts of modified quartz sand, and 0.7 parts of modified caged polysilsesquioxane by mass, let the No. 70 Grade A road asphalt stand at 135°C for 15 min, add modified quartz sand, pre-modified epoxy polymer and modified caged polysilsesquioxane in sequence, stir at 800 r / min for 40 min, cool to 90°C, and let stand for 40 min to obtain asphalt mortar.
[0026] Test Example 1: Aging resistance and self-repair test: Self-repair test: the asphalt mortar prepared in each embodiment and comparative example was allowed to stand at 150°C for 2 hours, and the asphalt mortar prepared in each embodiment and comparative example was made into a standard dumbbell-shaped specimen according to the requirements of GB / T2568-1995, and the tensile strength was tested, which was recorded as the initial tensile strength; then a small cut of 3 mm in length and 3 mm in depth was cut in the middle of the same specimen, and the fractures were aligned and spliced after cutting, and placed in a constant temperature oven at 145°C for 2 hours, and the tensile strength of the repaired specimen was tested, which was recorded as the tensile strength after self-repair; the self-repair efficiency was calculated, wherein the self-repair efficiency = tensile strength after self-repair / initial tensile strength × 100%; Aging resistance test: The asphalt mortar prepared in each embodiment and comparative example was left to stand at 150°C for 2 hours. Referring to the requirements of GB / T2568-1995, the asphalt mortar prepared in each embodiment and comparative example was made into a standard dumbbell-shaped specimen, and the tensile strength was tested, which was recorded as the initial tensile strength; the same specimen was irradiated under a fluorescent ultraviolet lamp UV-A340 for 15 days, and the tensile strength was tested again, which was recorded as the tensile strength after aging; the tensile strength retention rate was calculated, where the tensile strength retention rate = tensile strength after aging / initial tensile strength × 100%. The results are shown in Table 1.
[0027] Table 1
[0028] From the comparison of the experimental data in Table 1, it can be found that the modified asphalt mortar for road repair prepared by the present invention has good aging resistance and self-repairing ability.
[0029] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the tensile strength retention rates of Examples 1, 2, and 3 are greater than that of Comparative Example 1, indicating that the introduction of 4-propyleneoxy-2-hydroxybenzophenone can absorb ultraviolet rays, and by absorbing ultraviolet light and converting it into heat energy, the material can be protected from damage by ultraviolet rays, thereby improving the aging resistance of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the self-repairing efficiency of Examples 1, 2, 3 is greater than that of Comparative Example 2, which indicates that the introduction of furan groups and maleimide groups into the asphalt mortar generates reversible bonds through the DA reaction between the two, thereby achieving a self-repairing effect.
[0030] Test Example 2: High temperature resistance test: The asphalt mortar prepared in each embodiment and comparative example was placed at 150°C for 2 hours, crushed to 30 mesh, 8 mg of asphalt was placed in a crucible and then placed in a TG experimental instrument to test the mass retention rate at 300°C, where the mass retention rate = mass at 300°C / 8 mg × 100%. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data in Table 2, it can be found that the modified asphalt mortar for road repair prepared by the present invention has good high temperature resistance.
[0033] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the mass retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 1, which shows that the surface of octaaminopropyl cage-like polysilsesquioxane is rich in aminopropyl groups, which reacts with epoxy groups to act as a curing agent. The introduction of octaaminopropyl cage-like polysilsesquioxane increases the cross-linking point density of the material, so that the material can better resist deformation and damage at high temperatures, thereby improving its heat resistance. In addition, octaaminopropyl cage-like polysilsesquioxane itself has high heat resistance, and its initial thermal decomposition temperature can reach above 350°C, which can effectively improve the heat resistance of the material.
[0034] Test Example 3: Waterproof test: The asphalt mortar prepared in each embodiment and comparative example was left to stand at 150° C. for 2 hours to prepare a sample of 4 cm×4 cm×0.1 cm, and the water surface contact angle was tested using a JC2000DM optical contact angle measuring instrument. The results are shown in Table 3.
[0035] Table 3
[0036] From the comparison of the experimental data in Table 3, it can be found that the modified asphalt mortar for road repair prepared by the present invention has good waterproof ability.
[0037] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 3, it can be found that the water contact angles of Examples 1, 2, and 3 are larger than that of Comparative Example 1, indicating that the octaaminopropyl cage-like polysilsesquioxane can form a tight, high-density hard coating film to prevent liquid from penetrating into the interior of the material and enhance the waterproof ability of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the water contact angles of Examples 1, 2, 3 are larger than that of Comparative Example 3, which indicates that fluorine is introduced onto the asphalt surface through the reaction with N-(trifluoromethylthio)phthalimide. The electronegativity of the fluorine atom is very large, so that the electron cloud in the carbon-fluorine bond is biased toward the fluorine atom, resulting in the carbon-fluorine bond having a very high bond energy, which is very stable and not easily destroyed by water or other chemicals, thereby enhancing the waterproof ability of the material.
[0038] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A modified asphalt mortar for road repair, characterized in that: The modified asphalt mortar for road repair is prepared by heating asphalt and mixing it with modified epoxy polymer, modified quartz sand and modified cage-like polysilsesquioxane; The modified epoxy polymer is prepared by polymerizing glycidyl methacrylate, N,N-dimethylpropyleneamine, and 2-allylfuran and then reacting with N-(trifluoromethylthio)phthalimide; The modified quartz sand is prepared by reacting quartz sand with 3-aminopropyltrimethoxysilane and maleic anhydride in sequence; The modified caged polysilsesquioxane is prepared by reacting 4-propyleneoxy-2-hydroxybenzophenone with octaaminopropyl caged polysilsesquioxane.
2. A method for preparing modified asphalt mortar for road repair, characterized in that: The preparation method of the modified asphalt mortar for road repair mainly includes the following preparation steps: (1) 4-propyleneoxy-2-hydroxybenzophenone and ethanol were mixed in a mass ratio of 1:20-22, stirred at 200-300 r / min and room temperature for 5-7 min, and an equal molar amount of octaaminopropyl caged polysilsesquioxane of 4-propyleneoxy-2-hydroxybenzophenone was added, the temperature was raised to 45-55°C, and stirring was continued for 3.5-4.5 h under argon protection, filtered, washed with ethanol 3-5 times, and dried to obtain a modified caged polysilsesquioxane; (2) Pre-modified quartz sand, maleic anhydride and N,N-dimethylformamide were mixed in a mass ratio of 3-5:1:16-18, stirred for 25-35 min at 85-95 °C, 200-300 r / min, and nitrogen protection, and a mixed solution of 1.8-2.2 times the mass of maleic anhydride was added, and the mixture was stirred for 35-45 min. The mixture was cooled to room temperature, poured into deionized water at 0-4 °C, and stirred for 11-13 h. The mixture was filtered and dried at 75-85 °C for 9-11 h to obtain modified quartz sand. (3) immersing the pre-modified epoxy polymer in a mixed solution of N-(trifluoromethylthio)phthalimide, irradiating with ultraviolet light for reaction, taking out, immersing in deionized water, ultrasonicating for 10 to 20 minutes, and drying at -10 to 0°C under vacuum conditions for 22 to 24 hours to obtain a modified epoxy polymer; (4) Allow the asphalt to stand at 130-140°C for 10-20 min, then add modified quartz sand, modified epoxy polymer and modified cage polysilsesquioxane in sequence, stir at 700-900 r / min for 35-45 min, cool to 85-95°C, and allow to stand for 35-45 min to obtain asphalt mortar.
3. The method for preparing a modified asphalt mortar for road repair according to claim 2, characterized in that: The specific operation of the drying in step (1) is vacuum drying at -10~0°C for 22~26h.
4. The method for preparing a modified asphalt mortar for road repair according to claim 2, characterized in that: The pre-modified quartz sand in step (2) is prepared by mixing quartz sand, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 3-5:1-2:30-50, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging, taking the solid, washing it with deionized water for 3-5 times, and drying it at 90-100°C for 2-4 hours.
5. The method for preparing a modified asphalt mortar for road repair according to claim 2, characterized in that: The mixed solution in step (2) is prepared by uniformly mixing nickel acetate tetrahydrate, triethylamine and acetic anhydride in a mass ratio of 0.001:0.3-0.4:40-45.
6. The method for preparing modified asphalt mortar for road repair according to claim 2, characterized in that: The pre-modified epoxy polymer in step (3) is prepared by mixing glycidyl methacrylate, N,N-dimethylpropyleneamine, 2-allylfuran, azobisisobutyronitrile and tetrahydrofuran in a mass ratio of 7-8:1:1-2:0.03-0.05:30-40, stirring at 200-300 r / min, 60-70° C., under nitrogen protection for 10-12 h, cooling to room temperature, pouring into methanol, standing for 3-5 h, filtering, and vacuum drying at 55-65° C. for 22-26 h.
7. The method for preparing modified asphalt mortar for road repair according to claim 2, characterized in that: The N-(trifluoromethylthio)phthalimide mixed solution in step (3) is prepared by uniformly mixing N-(trifluoromethylthio)phthalimide, acetonitrile and benzophenone in a mass ratio of 7-8:49-53:0.5-1.
8. The method for preparing modified asphalt mortar for road repair according to claim 2, characterized in that: The specific operation of the ultraviolet light irradiation reaction in step (3) is to place the reaction mixture in a closed photoreactor under nitrogen protection and irradiate it with a 40W purple LED lamp with a wavelength of 370nm for 48 to 50 hours.
9. The method for preparing modified asphalt mortar for road repair according to claim 2, characterized in that: The raw material composition ratio of the asphalt mortar prepared in step (4) is asphalt: modified epoxy polymer: modified quartz sand: modified cage-like polysilsesquioxane in a mass ratio of 8-10: 1.8-2.2: 2.6-3: 0.6-0.8.
Citation Information
Patent Citations
Asphalt modifying agent and modified asphalt
CN106398247A
Anti-skid surface layer of asphalt pavement and construction method of anti-skid surface layer
CN116640455A
Modified sand mastic asphalt compositon and construction method thereof
KR102136233B1